Czy Hermogenes oglądałby telewizję? – starożytny podręcznik dla medioznawców - Kampka, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
The purpose of this article is to examine whether the work of Hermogenes can be useful in the analysis of the media. The Polish translation of the Byzantine textbook becomes an opportunity to reflect on the universality of the principles of creating persuasive messages. According to Hermogenes, rhetoric is the practical, civic skill of persuasion on important matters. Today, his ideas can be applied to television news. His textbook teaches us how to analyse the structure of television programmes, how to find – at a verbal and visual level – rhetorical figures.